The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3389/fncel.2016.00286
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Characterization of Microglia/Macrophage Phenotypes in a Mouse Model of Neonatal Hypoxic-Ischemic Brain Injury

Abstract: Immune cells display a high degree of phenotypic plasticity, which may facilitate their participation in both the progression and resolution of injury-induced inflammation. The purpose of this study was to investigate the temporal expression of genes associated with classical and alternative polarization phenotypes described for macrophages and to identify related cell populations in the brain following neonatal hypoxia-ischemia (HI). HI was induced in 9-day old mice and brain tissue was collected up to 7 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
72
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 88 publications
(82 citation statements)
references
References 41 publications
(55 reference statements)
8
72
2
Order By: Relevance
“…In our study, analyses at 72 h after the injury showed no significant differences in the levels of several pro-inflammatory cytokines. This could be attributed to our experimental design of the evaluation of pro-inflammatory cytokines at the end of the sub-acute phase [3,62]. We found differences in the antiinflammatory cytokines between DTA − and DTA + mice.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In our study, analyses at 72 h after the injury showed no significant differences in the levels of several pro-inflammatory cytokines. This could be attributed to our experimental design of the evaluation of pro-inflammatory cytokines at the end of the sub-acute phase [3,62]. We found differences in the antiinflammatory cytokines between DTA − and DTA + mice.…”
Section: Discussionmentioning
confidence: 86%
“…Neonatal hypoxic-ischemic encephalopathy (HIE) is a major worldwide cause of neonatal death and long-term disability, including mental retardation, visual motor or visual perceptive dysfunction, hyperactivity, cerebral palsy, and epilepsy. HI insults are known to induce inflammatory reactions within hours in rodent models with microglia playing an important role [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Neuroinflammation includes complex changes in microglial phenotypes, mediated by gene expression changes leading to the production of cytokines and chemokines and production of ROS. Altogether this triggers oxidative and nitrosative stress in the brain (Bolouri et al, ; Hellström Erkenstam et al, ). We observed as expected that LPS‐activated microglia produced a plethora of chemokines and cytokines and ROS.…”
Section: Discussionmentioning
confidence: 99%
“…In the HI brain, there is also a considerable contribution of infiltrating peripheral immune cells to the brain after injury (Hellstrom Erkenstam et al, 2016). Next, we investigated the effect of PUR administration on infiltrating monocytes/neutrophils (CD11b + /CD45 high cells).…”
Section: Pur Suppressed Neuro-inflammation Following Hi Insultmentioning
confidence: 99%